Cooperation of internal and external audit - Zabawa, Gabriela (SPC Journal of Education, 2020)
This article addresses the issue of cooperation between internal and external auditing, their similarities and differences, as well as the areas in which they complement each other. It presents the main assumptions and objectives of audits, their functions and shows the importance of integrating both of audits to increase company efficiency and thoroughly examine purposefulness and correctness of ongoing processes.Â Â